ANALYSIS OF FLOOD HAZARDS IN BANGER LAMA DRAINAGE SYSTEM, PEKALONGAN CITY: THE INFLUENCE OF RAINFALL, SEA LEVEL RISE, AND LAND SUBSIDENCE - Iqbal Huseiny, Moh.
The coastal area of Pekalongan City faces serious challenges due to frequent flooding and tidal inundation. The low and flat topography of the area makes it difficult to manage the drainage system due to the relatively small slope of the land. Flooding incidents often occur in various parts of Pekalongan City, while the threat of tidal inundation is increasing in the northern coastal area. The global sea level rise and land subsidence in the region further exacerbate these problems. This study aims to model the drainage system considering the influence of rainfall, sea level rise, and land subsidence in Pekalongan City. The methods employed include hydrological analysis, tidal analysis, land subsidence analysis, and sea level rise analysis. The modeling is conducted using the Personal Computer Storm Water Management Model (PCSWMM) software with various scenarios of rainfall, sea level rise, and land subsidence. The modeling outcomes include flood depth maps, flood velocity maps, and flood duration maps. Furthermore, flood threat maps are developed using the Flood Hazard Index method, which combines the three parameters in each scenario. Proposed flood mitigation solutions include the construction of embankments and flap gates in the flood-prone upstream areas, as well as modifications to the drainage system by implementing gravity flow without pumps in the downstream areas. However, it should be noted that these recommendations may not be effective in scenarios with significant land subsidence. This study is expected to assist stakeholders in making informed decisions regarding the management of the drainage system in Pekalongan City, thereby reducing the impacts of flooding in the area.